"Maybe if they let us tell the story I wouldn't have gotten suspended": Understanding Black students' and parents' perceptions of school discipline. (March 2020) - Bell, Charles
Highlights: Black students perceive school discipline as unfair because their voices are ignored. Black students expressed feelings of being targeted for suspension. Excessive school discipline led Black parents to abandon a district. Abstract: While studies confirm educators and administrators suspend Black students from school at disproportionate rates, few have explored Black students' and their parents' perceptions of school discipline. Using Critical Race Theory as a framework, I interview thirty Black students and thirty parents of Black students who received an out-of-school suspension from a primarily Black high school (PBHS) in southeast Michigan during the 2016–2017 academic year. My findings suggest Black students and their parents perceive out-of-school suspension as unfair because (a) school officials marginalize their voices throughout the disciplinary process, and (b) students feel school officials target them for out-of-school suspension based on their style of dress, hair, and music preference. My findings also show out-of-school suspension is associated with "Black educational flight, " a process in which parents withdraw their children from PBHSs in response to excessive out-of-school suspension and enroll them in schools that are perceived to be less punitive.